2010
DOI: 10.1016/s0034-7094(10)70002-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Ultrasound to Determine the Level of Lumbar Puncture in Pregnant Women

Abstract: The L3-L4 space is correctly identified in a low percentage of obese and non-obese pregnant women. Spinal ultrasound can reduce the incidence of mistaken identification of the L3-L4 space in obese and non-obese pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
2
32
2
3
Order By: Relevance
“…23 Palpation of lumbar spinous processes is inaccurate in both lean and obese patients, and inferior in prediction of lumbar level compared to ultrasound. [24][25][26][27][28] It is not clear if routine use of ultrasound guidance in lean patients is superior to landmark-based LP. 15,29 As a multidisciplinary panel of procedural experts from different institutions, we concur with a recent recommendation for routine use of ultrasound guidance for patients in whom risk of a failed procedure is high due to poorly palpable landmarks or atypical spinal anatomy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…23 Palpation of lumbar spinous processes is inaccurate in both lean and obese patients, and inferior in prediction of lumbar level compared to ultrasound. [24][25][26][27][28] It is not clear if routine use of ultrasound guidance in lean patients is superior to landmark-based LP. 15,29 As a multidisciplinary panel of procedural experts from different institutions, we concur with a recent recommendation for routine use of ultrasound guidance for patients in whom risk of a failed procedure is high due to poorly palpable landmarks or atypical spinal anatomy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Biorąc pod uwagę fakt, że tradycyjne metody wykorzystujące znajomość anatomii i anatomicznych punktów orientacyjnych w większości przypadków umożliwiają wykonanie skutecznej blokady centralnej, a także uwzględniając, że okolica kręgosłupa u pacjentów dorosłych jest trudna do obrazowania ultrasonograficznego ze względu na dużą ilość struktur kostnych, USG w tym obszarze nie stosuje się tak często jak w przypadku blokad obwodowych. Ostatnio w piśmiennictwie pojawiło się jednak wiele prac wykazujących korzyści związane z wykorzystaniem tej techniki w blokadach centralnych, szczególnie w przypadku kobiet ciężarnych [8][9][10][11][12]. Wszyscy autorzy wskazują na rozbieżność w ocenie na podstawie badania przedmiotowego oraz obrazu ultrasonograficznego w tej grupie pacjentek.…”
Section: Dyskusjaunclassified
“…Ultrasonografia jest stosowana do określenia położenia splotów i nerwów obwodowych, jak również do wyznaczenia wysokości przestrzeni międzykręgowych oraz oceny głębokości położenia przestrzeni zewnątrzoponowej i podpajęczynówkowej. Jak wskazują wyniki badań, ocena wysokości przestrzeni międzykręgowych na podstawie anatomicznych punktów orientacyjnych jest często rozbieżna z oceną dokonaną według obrazowania ultrasonograficznego [8][9][10][11][12].…”
unclassified
“…It should be noted that both Furness et al (12) and Whitty et al (13) investigated subjects with a range of body weights and not specifically on obese subjects. In a more recent study by de Figueiredo Locks et al, no significant differences were found when obese and non-obese obstetric patients were compared in terms of accuracy in locating the L3-L4 IVS (14).…”
Section: Original Research Articlementioning
confidence: 87%
“…This could have affected our results when we compared anaesthesiologists of various levels of experience. Lastly, in order to better appreciate the difficulties encountered in obese subjects, a "control" group of non-obese individuals could have been included in our study, as was done in the study by de Figueiredo Locks et al (14).…”
Section: Discussionmentioning
confidence: 99%